Implementation Of Democracy In The Village: A Case Study Of The Village Head Election In Ciheulang Village - Addinari, Shabina Sundus; Maharani, Dhinda Dwi; Finanda, Azril Alfian (Universitas Ibn Khaldun Bogor, 2025)
This study analyzes the implementation of democratic values in the 2019 Village Head Election (Pilkades) in Ciheulang Village, Bandung Regency. Despite achieving a high voter turnout (74.6%), the election process was characterized by social fragmentation, money politics, and a lack of post-election reconciliation mechanisms. Using a qualitative case study approach, data were collected through interviews with key stakeholders and documentation analysis. The results indicate that while participation was high, voter behavior was often influenced by personal ties rather than rational consideration of candidates’ programs. This highlights a gap between procedural and substantive democracy. To enhance democratic quality at the village level, the study recommends improving political literacy and formalizing post-election conflict resolution processes.